2009
DOI: 10.2478/v10007-009-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solvatomorphs of methotrexate using thermoanalytical and other techniques

Abstract: Investigation of polymorphism and solvatomorphism in drug molecules is an important step in any pre-formulation program from both biopharmaceutical and technological point of view (1, 2). It is well known that polymorphs are different crystalline forms of the same compound whereas the inclusion of a solvent in a crystal lattice gives rise to pseudopolymorphs or solvatomorphs (2). One of the most relevant features among polymorphic modifications is the difference in their solubility and dissolution rate that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
3
21
0
2
Order By: Relevance
“…4 shows XRD analysis for different samples. Unprocessed methotrexate occurred in a crystalline state, which was attributed to well-defined diffraction peaks at 2θ of 7.6 and 9.2, characteristic of its trihydrate form [10,19]. In accordance with some reported studies, in the XRD of chitosan diffraction peaks were observed at 10°or 20°corresponding to hydrated and anhydrous crystals respectively [20,21].…”
Section: Resultssupporting
confidence: 89%
“…4 shows XRD analysis for different samples. Unprocessed methotrexate occurred in a crystalline state, which was attributed to well-defined diffraction peaks at 2θ of 7.6 and 9.2, characteristic of its trihydrate form [10,19]. In accordance with some reported studies, in the XRD of chitosan diffraction peaks were observed at 10°or 20°corresponding to hydrated and anhydrous crystals respectively [20,21].…”
Section: Resultssupporting
confidence: 89%
“…Further, a broad peak at 240-270 C was also verified due to the decomposition of the MTX, which overlapped the melting endotherm of the drug. The obtained results corroborated with those previously described (Chan & Gonda, 1991;Chadha et al, 2009). For the MTX PCL implants (Figure 3d), the DSC thermogram showed all endothermic events corresponding to the PCL and the drug.…”
Section: Characterizationsupporting
confidence: 92%
“…Changqun et al studied and analyzed how the Methotrexate molecule interacts with nucleic acids by multi-spectroscopic method [9]. Recently, identification and characterization of different forms of Methotrexate were carried out by crystallization from different solvents by Chadha et al [10]. The crystal and molecular structure of Methotrexate were reported by Hambley et al [11] and Mastrapolo et al [12].…”
Section: Methotrexatementioning
confidence: 98%